2020
DOI: 10.5114/jcb.2020.96869
|View full text |Cite
|
Sign up to set email alerts
|

Single-fraction low-energy electronic brachytherapy for conjunctival lymphoma

Abstract: Purpose Conjunctival lymphoma represents an uncommon tumor, accounting for 5-10% of total extranodal lymphomas. Although radiotherapy is a frequent treatment option, limited capacities and lack of specialized centers are common problems in Peru, forcing radiation oncologists to apply short courses of radiotherapy. Here, we report a case series of patients treated with a novel single-shot scheme. Additionally, we present a literature review of the current short-course irradiation strategies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In addition, IMRT patients had significantly fewer acute toxicities and a trend toward lower late toxicities, compared to 3D-CRT or electrons patients. Three cases of conjunctival MALT of the fornix were treated with a focused single dose of 14 Gy kilovoltage brachytherapy that prescribed to the maximum thickness of the lesion, and after 40 months of follow-up, none of the three patients treated had any acute or chronic toxicities and were disease-free locally and distantly [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IMRT patients had significantly fewer acute toxicities and a trend toward lower late toxicities, compared to 3D-CRT or electrons patients. Three cases of conjunctival MALT of the fornix were treated with a focused single dose of 14 Gy kilovoltage brachytherapy that prescribed to the maximum thickness of the lesion, and after 40 months of follow-up, none of the three patients treated had any acute or chronic toxicities and were disease-free locally and distantly [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al demonstrated in a large cohort study that lower RT dosing (≤25.2Gy vs. >25.2Gy) significantly correlates with lower cataract rates while not leading to increased relapse 26 . Case series and retrospective studies utilizing ultra‐low‐dose RT (4Gy) have reported promising local control results and low toxicity profile; however, prospective and long‐term follow‐up studies are still lacking 43–45 . A retrospective study from Japan demonstrated that lens shielding could reduce the incidence of cataracts by half 46 .…”
Section: Discussionmentioning
confidence: 99%
“…26 Case series and retrospective studies utilizing ultra-low-dose RT (4Gy) have reported promising local control results and low toxicity profile; however, prospective and long-term follow-up studies are still lacking. [43][44][45] A retrospective study from Japan demonstrated that lens shielding could reduce the incidence of cataracts by half. 46 In addition to its protective effect, the use of lens shielding also helps build up the RT dose focused on the lesion site.…”
Section: Discussionmentioning
confidence: 99%